2009
DOI: 10.1039/b820970g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic coating- and surface active solvent-mediated self-assembly of charged gold and silver nanoparticles at water–air and water–oil interfaces

Abstract: We report self-assembly of charge-stabilized gold and silver nanoparticles at water-air and water-oil interfaces, via manipulation of the interactions between the interfaces and the adsorbing nanoparticles. Nanoparticle adsorption from bulk colloids to an interface is an energy-favored, but finite sorption barrier-restrained (kinetics-controlled) process. Consequently, to successfully mediate self-assembly of nanoparticles, the finite sorption barrier should be decreased. That can be accomplished by manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 58 publications
1
63
0
1
Order By: Relevance
“…2 shows the SEM images for the Ag NP thin film welded by light irradiation for different duration. As observed previously, the NP thin film assembled at the water-air interface shows a typical monolayer structure dotted with small voids [9,28,30]. Before light welding, most NPs only physically contact with each other, with abundant inter-particle junctions in the range of 1-5 nm.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…2 shows the SEM images for the Ag NP thin film welded by light irradiation for different duration. As observed previously, the NP thin film assembled at the water-air interface shows a typical monolayer structure dotted with small voids [9,28,30]. Before light welding, most NPs only physically contact with each other, with abundant inter-particle junctions in the range of 1-5 nm.…”
Section: Resultsmentioning
confidence: 67%
“…After their synthesis, cyclohexane (5 mL) was gently covered on the surface of the metal colloids (20 mL) to produce a sharp water-oil interface. Upon quick addition of ethanol (1.5 mL), the metallic NPs in the colloids were induced to the wateroil interface, where they were trapped and spontaneously self-assembled into an NP thin film with metallic luster [9,28]. After careful removal of the oil using a syringe, the metallic NP thin film was left at the water-oil interface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaeger and co-workers demonstrated that highly ordered two-dimensional gold nanoparticle films could be fabricated by a simple direct-drying method, either at the toluene-water interface or toluene-air interface (Figure 7 e, f). [66,67] Other ligand-capped gold nanoparticles, [26,68] FePt nanoparticles, [69] silver nanoparticles, [70] CoPt 3 nanoparticles, [71] and g-Fe 2 O 3 nanoparticles [26] can also self-assemble at the oil-water interface and form thin films.…”
Section: Thin Films At Liquid-liquid Interfacesmentioning
confidence: 98%
“…13 According to the extended DLVO model (Derjaguin and Landau, Verwey and Overbeek), [14][15][16] the attractive long-range forces might be electrostatic forces (if the nanoparticles and the surface have opposite charges) or acid-base interaction forces (due to the interaction of polar groups in water). As the zeta-potential of the Au NPs and the surface were both negative (see ESI for details †), the attractive forces could be attributed mainly to the acid-base and Lifshitz van der Waals interactions.…”
Section: Immobilization Of Au Nps On Peo-like Coatingsmentioning
confidence: 99%